2021
DOI: 10.3390/mti5080046
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and User Behavior in Online Science Laboratories before and during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has resulted in the closure of schools at every level, globally, forcing education to move online. Meeting the needs of students online for Science Lab classes, in particular, is a challenge since the physical labs are not available to the teachers or students. OLabs is a virtual Science Lab providing a complete learning environment of theory, experimental procedures, videos, animations, simulations, and assessments that capture real lab experiences with the relevant pedagogy. This study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…COVID-19 has sparked the importance of virtual labs substantially in higher education due to sporadic shutdowns, online coverage of technical content, and inaccessibility of physical labs. In this health-induced economic crisis, virtual labs play a crucial role in the experimentation, analysis, and higher education of students in the sciences field (Ray & Srivastava, 2020 ; Raman et al, 2021b ). Initially, before COVID, behavioral analysis on university students indicated the substantial popularity of virtual laboratories in education for skill training and instructor dependency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…COVID-19 has sparked the importance of virtual labs substantially in higher education due to sporadic shutdowns, online coverage of technical content, and inaccessibility of physical labs. In this health-induced economic crisis, virtual labs play a crucial role in the experimentation, analysis, and higher education of students in the sciences field (Ray & Srivastava, 2020 ; Raman et al, 2021b ). Initially, before COVID, behavioral analysis on university students indicated the substantial popularity of virtual laboratories in education for skill training and instructor dependency.…”
Section: Resultsmentioning
confidence: 99%
“…The virtual labs played a crucial role in the higher education sector during the COVID-19 pandemic. Using Google Analytics, Raman et al ( 2021a , 2021b , 2021c ) found that users increasingly adopted online labs during the pandemic as a new learning pedagogy for performing lab experiments as indicated by parameters such as the number of users; the number of unique pages viewed per session; time spent on viewing content and bounce rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, though Australia and the UK have almost similar publications, the citations are significantly higher for Australian publications, nearly 67% more. These numbers show the importance of bibliographic studies in identifying the significance of publications, critical research groups, etc., instead of just assessing the number of publications [74], [75].…”
Section: Covid-19 Related Research In Iamentioning
confidence: 99%